Deep Venous Thrombosis and Bilateral Pulmonary Embolism Revealing Silent Celiac Disease: Case Report and Review of the Literature - Igor Dumic; Scott Martin; Nadim Salfiti; Robert Watson; Tamara Alempijevic (Case Reports in Gastrointestinal Medicine)
Celiac disease (CD) is a systemic, chronic autoimmune disease that occurs in genetically predisposed individuals following dietary gluten exposure. CD can present with a wide range of gastrointestinal and extraintestinal manifestations and requires lifelong adherence to a gluten-free diet [GFD]. Venous thromboembolism (VTE) as a presentation of celiac disease is unusual and rarely reported. We present a case of a 46-year-old man who was admitted for shortness of breath and pleuritic chest pain and was found to have iron deficiency anemia, deep venous thrombosis, and bilateral pulmonary emboli (PE). After work-up for his anemia, the patient was diagnosed with CD. Comprehensive investigation for inherited or acquired prothrombotic disorders was negative. It is becoming increasingly recognized that CD is associated with an increased risk for VTE. PE, however, as a presentation of CD is exceedingly rare and to the best of our knowledge this is the third case report of such an occurrence and the only case report of a patient from North America. It is important to recognize that the first symptoms or signs of celiac disease might be extraintestinal. Furthermore, VTE as a presentation of CD is rare but life-threatening.